Development of supported nickel-based catalysts for deoxygenation of waste cooking oil to renewable fuel production - Wan Khalit, Wan Nor Adira (2022)
The development of renewable diesel fuel from the deoxygenation of non-edible oil is an alternative to non-renewable fuels. This study investigated the catalytic deoxygenation of waste cooking oil (WCO) over supported Ni-based catalysts. The deoxygenation of WCO was conducted using different types of supports: activated carbon (AC), reduced graphene oxide (rGO), and beta zeolite (Zeo). The addition of Ni to AC improves the physicochemical properties of the catalyst, owing to the high number of acid-base sites, high surface area, smaller crystallite size, and high pore volume of the catalyst. Based on the catalytic results, Ni20/AC was the most active catalyst, which achieved 90% hydrocarbon yield and 89% selectivity towards n-(C15+C17). Furthermore, it was stable up to the fourth cycle with consistent hydrocarbon yield (85-87%) and 66- 77% selectively towards n-(C15+C17). Further investigation was conducted to study the effect of bifunctional catalysts (NiLa, NiCe, NiFe, NiMn, NiZn, and NiW) supported on AC. High hydrocarbon yield above 60% with lower oxygenated species was found in the liquid product with the product selectively toward n-(C15+C17)-diesel fractions. The predominance of n-(C15+C17) hydrocarbons with concurrent production of CO and CO2 indicated that the deoxygenation pathway preceded via decarbonylation and decarboxylation mechanisms. For NiLa/AC, high deoxygenation activity with better n- (C15+C17) selectivity was obtained due to great synergistic interaction between La–Ni, and its compatibility of acid-base sites increased the removal of oxygenates. For the effect of La on the deoxygenation performance, it was found that a high percentage of La species would be beneficial in the removal of C-O bonded species. Furthermore, optimum deoxygenation activity of 88% hydrocarbon yield with 75% n-(C15+C17) selectivity was obtained over 20% La, which strongly evinced that La leads to more significant enhancement of deoxygenation activity. The NiLa/AC reusability study showed consistent deoxygenation with 80% hydrocarbon yield and 60% n-(C15+C17) hydrocarbons selectivity within six runs. As the NiZn/AC catalyst also showed high performance in deoxygenation activity, the optimization over a series of Ni20Znx/AC catalysts (X: 5–20 wt.%) was also studied. The Ni20Zn10/AC catalyst exhibited superior deoxygenation activity by yielding 86% hydrocarbons and 79% of n-(C15 + C17) selectivity. High deoxygenation activity is corroborated by the higher acidity and basicity strength of the catalyst and the oxygenate species removal that occurred via decarbonylation pathway. The Ni20Zn10/AC catalyst showed promising catalytic stability and reusability up to four runs with hydrocarbon yield (78 – 87%) and n-(C15 + C17) selectivity within the range of 43 – 70%, respectively. The decrease in the n-(C15 + C17) selectivity in the fourth cycle was due to the active metal species leaching and coking. In conclusion, all Ni-based catalysts demonstrated significant catalytic activity and reusability for green diesel production.